Moving Up the Ladder? The Impact of Migration Experience on Occupational Mobility in Albania - Carletto, Calogero (2012)
The contribution of return migrants to economic development in source countries can be significant. Overseas savings of returnees may lead to improvements in household welfare and provide liquidity for investments in the face of credit market failures. Labor market experience and skills acquired abroad may also lead migrants to find occupations higher in the skill and remuneration spectrum upon return. This study uses the 2005 Albanian Living Standards Measurement Study Survey and estimates the impact of international migration experience on the occupational mobility of return migrants vis a vis working-age Albanian residents that never migrated. Controlling for the non-random nature of international migration and return, the results show that past migration experience increases the likelihood of upward occupational mobility. Exploring the heterogeneity of impact by host country indicates that the positive effect of past migration experience on upward occupational mobility is driven by past migration experience in Italy and countries further a field, while past migration experience in Greece does not exert any significant impact on mobility outcomes. The results, which are consistent across different sample specifications and outcome variables measuring occupational mobility, hint at the link between migration and human/financial capital formation among migrants and foster optimism concerning the positive effect of return migration on economic development. This insight is particularly important since remittances from permanent migrants, which have fueled the impressive growth performance of the country in the recent era, may taper off in the medium to long term with the decline in out-migration and growing global economic woes.